Gamification in English education: Boosting motivation and language achievement - Farah Sukmawati Wahidah; Devi Mulatsih; Padaig Maeve Nowlan (Early Publishing Group, 2026)
Gamification has emerged as an innovative approach in English education, addressing persistent challenges related to low student motivation and limited language achievement. Current research highlights the potential of game-based elements—such as points, badges, and leaderboards—to enhance engagement and participation; however, many studies focus primarily on motivation or short-term outcomes rather than measurable improvements in language proficiency. This gap indicates a need for empirical evidence that directly connects gamification with both motivational and performance-based outcomes in structured classroom settings. This study aims to examine the impact of gamified English learning activities on students’ motivation and language achievement. Employing an experimental design, the study involved 60 undergraduate students divided into a gamified group and a non-gamified group. Data were collected through motivation surveys, language achievement tests, and classroom observations over a six-week intervention period. Quantitative data were analyzed using descriptive statistics and independent-samples t-tests with SPSS to determine significant differences between groups. The findings reveal that students in the gamified group demonstrated significantly higher motivation, reflected in greater enthusiasm, persistence, and participation. In addition, they achieved substantially higher language performance scores, showing improvements in accuracy, fluency, and task completion. Statistical results confirmed that these differences were highly significant, with large effect sizes in both motivation and achievement. These results suggest that gamification not only enhances engagement but also translates into measurable learning outcomes. The study implies that integrating well-designed game elements into English instruction can create a more interactive, motivating, and effective learning environment. This research contributes to the field by providing empirical evidence linking motivation and achievement, offering practical guidance for educators seeking to improve both student engagement and language proficiency through gamified learning strategies.